The Drosophila Larval Locomotor Circuit Provides a Model to Understand Neural Circuit Development and Function - Hunter, Iain; Coulson, Bramwell; Zarin, Aref Arzan; Baines, Richard A. (Frontiers in Neural Circuits, 2021)
It is difficult to answer important questions in neuroscience, such as: “how do neural circuits generate behaviour?”, because research is limited by the complexity and inaccessibility of the mammalian nervous system. Invertebrate model organisms offer simpler networks that are easier to manipulate. As a result, much of what we know about the development of neural circuits is derived from work in crustaceans, nematode worms and arguably most of all, the fruit fly, Drosophila melanogaster. This review aims to demonstrate the utility of the Drosophila larval locomotor network as a model circuit, to those who do not usually use the fly in their work. This utility is explored first by discussion of the relatively complete connectome associated with one identified interneuron of the locomotor circuit, A27h. Next, it is developed by examining its application to study two important areas of neuroscience research: critical periods of development and interindividual variability in neural circuits. In summary, this review highlights the potential of work conducted in the larval locomotor network to provide fundamental insight into circuit function that may contribute to better treatment, or cure, of disorders of neurodevelopment such as epilepsy and autism.